ISOLASI DAN SELEKSI BAKTERI FILOSFER PEMICU TUMBUH DARI DAUN PADI (ORYZA SATIVA L.) VARIETAS IR-64 - D.A Santosa; N Handayani; Iswandi Anas (Jurnal Ilmu Tanah dan Lingkungan, 2003)
Phylosphere bacteria are bacteria that live on the leave surface. Phylosphere bacteria have been reported to improve the growth of several plants such as rice. However, in Indonesia, the study concerning phylosphere bacteria is very rare. The aims of this study were to isolate and select phylosphere bacteria which are able to stimulate the growth of rice cultivar IR-64. Phylosphere bacteria were isolated from leaves of rice cultivar lR-64 grown at Ciherang (Sindangbarang) and at Pasirkuda (Ciomas) Bogor at the age of two, four and eight weeks after planting. The media used to isolate the phylosphere bacteria was Agar Ashbey. The surface of rice seeds was sterilized and then inoculated by deeping the rice seeds into bacterial suspension with a cell density of 1 x 106 cells ml-1. Leave inoculation was done by deeping leaves of three weeks old rice seedling into bacterial suspension with a cell density of 1 x 106 cells ml-1. Parameters measured were plant height, upper part biomas and root biomas. Phyllosphere bacteria were identified based on Bergey's Manual of Determinative Bacteriology. Nineteen isolates of phyllosphere bacteria were isolated from rice leaves, nine isolates were from Pasirkuda (Ciomas) and ten isolates were from Ciherang (Sindangbarang); eleven isolates were from rice phyllosphere and eight isolates were from endophyllosphere. Based on the age of the rice, two isolates were from two weeks old rice, nine isolates were from four weeks old rice and eight isolates were from eight weeks old rice. Phyllosphere bacteria significantly increased the plant height, upper parts biomass as well as root biomass. Six isolates were able to improve the growth of rice seedling IR-64 were Aureobacterium seperdae (two isolates), Arthrobacterium globiformis (one isolate) and Microbacterium lacticum (three isolates). Keywords: endophyllosphere, phyllosphere bacteria, rice cultivar IR-64